EP 137. The influence of age on hemispheric connectivity, a combined TMS and DTI study. Issue 9 (September 2016) - Grothe, M.; Strauss, S.; Lotze, M.; Domin, M.
Abstract : Background: Age effects both functional and structural brain function. Here, we combine two different methods to assess the impact of age on the neurophysiological and structural measurements of interhemispheric motor connectivity. We expect to find a clear association between both connectivity parameters and age. Methods: 15 participants between 22 and 72 years (median 36 years) participated in this study. Ipsilateral silent period (ISP) was collected from both dominant and non-dominant first dorsal interosseus (FDI) muscle. Structural M1-M1 connectivity was calculated using probabilistic tractography (fMRI software library, FSL). Interhemispheric M1-M1 tract volume and mean fractional anisotropy (FA) of the tract were calculated between dominant and non-dominant M1 and vice versa. We tested associations between ISP depth, tract volume and FA and age by calculating Pearson correlations. Results: ISP of the dominant hand correlated negatively with age ( r = −0.54; p < 0.05), and tract volume (non-dominant to dominant M1) with age showed a trend ( r = −0.48; p = 0.08). The correlation between ISP of the dominant hand and the tract volume for non-dominant to dominant M1 were positively correlated ( r = 0.57; p < 0.05). Discussion: As expected, we found an association of age on the interhemispheric connectivity in both neurophysiological and structural MRI measurements. Interestingly, the effect was only present from the non-dominant to the dominant hemisphere, and not in the other direction. In addition, interhemispheric inhibition was associated with tract volume, but not with averaged FA values of the tract, and again, only in the direction from the non-dominant to the dominant hemisphere. Our findings indicate that the age-related changes in interhemispheric connectivity are different between the dominant and non dominant primary motor cortex. Furthermore, the data suggest that the age-related interhemispheric tract volume loss may be the underlying cause of the age-related decrease of interhemispheric inhibition.